2021
DOI: 10.3389/fpsyt.2021.734986
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Expectation for Pain Relief on Orofacial Pain Treatment Outcomes

Abstract: Aims: To examine the effects of expectations for pain relief on the objective and subjective outcome of chronic orofacial pain (OFP) treatment.Materials and Methods: Sixty individuals referred to the Orofacial Pain Clinic at the Hebrew University-Hadassah School of Dental Medicine between 2015 and 2017 with OFP reported their expectation for pain relief upon initial consultation. They were also interviewed by telephone after treatment and asked to recall their expectations, referred to as “recalled expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Differences in pain characteristics between majority and minority groups may be attributed to expectations for pain relief [9], social inequality and racial bias. It was suggested that this inequality leads to inadequate medical care and prolonging the sensation of pain [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in pain characteristics between majority and minority groups may be attributed to expectations for pain relief [9], social inequality and racial bias. It was suggested that this inequality leads to inadequate medical care and prolonging the sensation of pain [35].…”
Section: Discussionmentioning
confidence: 99%
“…Pain experience can be influenced by ethnic factors like socioeconomic status, expectations language, spirituality, etc. [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle modifications may include avoiding triggers, maintaining regular sleep patterns, and employing stress-reduction techniques such as meditation or yoga. Naturally, success depends on individuals’ expectations and coping strategies [ 11 ]. Medications commonly used to manage migraines can be effective for NVOP.…”
mentioning
confidence: 99%
“…I am pleased to introduce this Special Issue on "Orofacial pain, diagnosis and treatment". Pain signals harm and induces behavioral changes, and chronic pain has a considerable emotional component [1]. The definition of pain, according to International Association for the Study of Pain (IASP), is "an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage".…”
mentioning
confidence: 99%